Computed Tomography Scanner Productivity and Entry-Level Models in the Global Market. (28th September 2017) - Santos, R. P.; Pires, A. L. A.; Almeida, R. M. V. R.; Pereira, W. C. A.
Abstract : Objective . This study evaluated the productivity of computed tomography (CT) models and characterized their simplest (entry-level) models' supply in the world market. Methods . CT exam times were measured in eight health facilities in the state of Rio de Janeiro, Brazil. Exams were divided into six stages: (1) arrival of patient records to the examination room; (2) patient arrival; (3) patient positioning; (4) data input prior to exam; (5) image acquisition; and (6) patient departure. CT exam productivity was calculated by dividing the total weekly working time by the total exam time for each model. Additionally, an internet search identified full-body CT manufacturers and their offered entry-level models. Results . The time durations of 111 CT exams were obtained. Differences among average exam times were not large, and they were mainly due to stages not directly related to data acquisition or image reconstruction. The survey identified that most manufacturers offer 2- to 4-slice models for Asia, South America, and Africa, and one offers single-slice models (Asia). In the USA, two manufacturers offer models below 16-slice. Conclusion . Productivity gains are not linearly related to "slice" number. It is suggested that the use of "shareable platforms" could make CTs cheaper, increasing their availability.